Atuação do agente comunitário de saúde durante a visita domiciliar na perspectiva do usuário - Araújo, Kárita Silva (2017)
The action of the Community Health Agent (ACS) with the population attached is an essential condition for the organization of public health services. However, it is necessary to know how this work is developed and the users' satisfaction with these activities. Within this perspective, this study aimed to understand the performance of the ACS during home visits from the perspective of the population served by the Family Health Strategy (ESF) in a medium-sized municipality in Goiás. This study was carried out in a municipality located in the state of Goiás, with medium size, with a sample composed of 400 families attended by the ACS of the municipality. The data collection instrument was composed of a structured questionnaire, whose questions sought to collect data that allowed to understand the work of the ACS in the community served. It was tried to verify if the scope of work defined by the National Basic Attention Policy (BANP) for the ACS is being fulfilled, in addition to the establishment of a link, in the user's perception, since these assignments should be performed by the ACS during the visit household (VD). The questionnaire was submitted to the Cronbach Alpha Test, whose value was 0.83. Data were submitted to associations test, Student's t-test and chi-square test. Regarding the work of the ACS during the VD, it was observed that the population understands that the RV is important, that the ACS are prepared to perform them and that the number of visits made to the family and the time dedicated to each of these visits are satisfactory. The satisfaction with the RV for families with people with disabilities obtained lower indexes. Regarding the relationship between the ACS and the population, it was identified that the families consider the work of the ACS and the VD to be important, in addition to declaring that they trust this professional. However, this confidence does not turn into a demand for ACS in case of illness in the family. Women up to 59 years of age do not seek ACS in case of illness in the family. Regarding the fulfillment of the assignments provided for in the PNAB, it was observed that approximately half of the participants are satisfied with the followup of the ACS in case of illness. Regarding the guidelines for healthy food and eating disorders, less than half of the participants expressed satisfaction with the ACS 'performance, as well as with the demand for adolescents involved in drugs and sex and with the conference on the criteria of the Bolsa Família program. The need to improve the performance of ACS was identified, but it was not possible to indicate which aspects should be improved. The services available at the Basic Health Unit (UBS) had a higher rate of user satisfaction (72.1%). These results demonstrate that the population knows the ACS and recognizes the importance of their work and the RV, but these feelings are not turning into action, such as the search for ACS in case of illness in the families. The population surveyed does not understand that the ACS is performing all its duties, as provided in the PNAB. Thus, it is observed that there is a wide field of actions, which can be developed by the ACS, aiming to contribute to the fulfillment of its actions, as foreseen in the PNAB.